Comparison of 3% Hypertonic Saline and 20% Mannitol for Reducing Intracranial Pressure in Patients Undergoing Supratentorial Brain Tumor Surgery: A Randomized, Double-blind Clinical Trial. Issue 2 (April 2018) - Ali, Achmet; Tetik, Aylin; Sabanci, Pulat A.; Altun, Demet; Sivrikoz, Nukhet; Abdullah, Taner; Aydoseli, Aydin; Sencer, Altay; Akinci, Ibrahim O.
Abstract : Background: In the present study, we hypothesized that 3% hypertonic saline (HS) is more effective than 20% mannitol to reduce intracranial pressure (ICP) and to modify brain bulk in patients undergoing an elective supratentorial craniotomy. Materials and Methods: After institutional review board approval, patients scheduled to undergo supratentorial craniotomy were enrolled into this prospective, randomized, double-blind study. The patients were monitored for routine hemodynamic parameters, depth of anesthesia, and ICP. They received 5 mL/kg 20% mannitol (n=20) or 3% HS (n=19) as infusion for 15 minutes. The patients' ICP values were monitored during hypertonic fluid infusion and throughout 30 minutes after infusion as a primary outcome. Secondary outcomes were hemodynamic variables, serum sodium value, blood gases, and surgeon brain relaxation assessment score (1=relaxed, 2=satisfactory, 3=firm, 4=bulging). In addition, the length of intensive care unit and hospital stay were recorded. Results: Demographic and tumor characteristics were similar between groups. The basal (before hypertonic infusion, ICPT0 ) and last (30 min after hypertonic infusion finished, ICPT45 ) ICP values were 13.7±3.0 and 9.5±1.9 mm Hg, respectively, for the M group, which were comparable with the corresponding levels of 14.2±2.8 and 8.7±1.1 mm Hg in the HS group ( P >0.05). The median amount of ICP reduction between T0 and T45 timepoints were 4 (1 to 7) and 5 (1 to 9) mm Hg for group M and group HS, respectively ( P =0.035). Baseline central venous pressure, pulse pressure variation, and serum sodium and lactate values were similar between groups, but the last measured pulse pressure variation and lactate value were lower, and sodium value was higher in group HS than in group M ( P <0.05). Duration of hospital and intensive care unit stay were similar between groups. Conclusions: Our results suggest that 3% HS provided more effective ICP reduction than 20% mannitol during supratentorial brain tumor surgery.